Dynein localization and pronuclear movement in the C. elegans zygote. Issue 12 (28th October 2022) - Ignacio, David P.; Kravtsova, Natalia; Henry, John; Palomares, Roberto Hernández; Dawes, Adriana T.
Abstract: Centrosomes serve as a site for microtubule nucleation and these microtubules will grow and interact with the motor protein dynein at the cortex. The position of the centrosomes determines where the mitotic spindle will develop across all cell types. Centrosome positioning is achieved through dynein and microtubule‐mediated force generation. The mechanism and regulation of force generation during centrosome positioning are not fully understood. Centrosome and pronuclear movement in the first cell cycle of the Caenorhabditis elegans early embryo undergoes both centration and rotation prior to cell division. The proteins LET‐99 and GPB‐1 have been postulated to have a role in force generation associated with pronuclear centration and rotation dynamics. When the expression of these proteins is perturbed, pronuclear positioning exhibits a movement defect characterized by oscillatory ("wobble") behavior of the pronuclear complex (PNC). To determine if this movement defect is due to an effect on cortical dynein distribution, we utilize RNAi‐mediated knockdown of LET‐99 and GPB‐1 to induce wobble and assay for any effects on GFP‐tagged dynein localization in the early C. elegans embryo. To compare and quantify the movement defect produced by the knockdown of LET‐99 and GPB‐1, we devised a quantification method that measures the strength of wobble ("wobble metric") observed under these experimental conditions. Our quantification of pronuclear complex dynamics and dynein localization shows that loss of LET‐99 and GPB‐1 induces a similar movement defect which is independent of cortical dynein localization in the early C. elegans embryo.